Volatility spillover effect and dynamic correlation between regional emissions allowances and fossil energy markets: New evidence from China's emissions trading scheme pilots. (15th October 2019) - Chang, Kai; Ye, Zhifang; Wang, Weihong
Abstract: This paper investigates the volatility spillover effects and dynamic correlations between China's emissions allowances and fossil energy markets by employing the dynamic conditional correlation (DCC) generalized autoregressive conditional heteroscedasticity (GARCH) model. Thermal coal futures, South Sea crude oil and liquefied natural gas markets confirm short-term and long-term persistence on the Beijing, Shanghai, Guangdong and Shenzhen emissions allowances pilots, while those fossil energy markets demonstrate long-term persistence on Hubei's emissions allowances pilot. The dynamic correlations between fossil energy and regional emissions allowance markets exhibit slight time-varying trends, and their dynamic correlations are at lower levels in the period considered. The prohibition of cross-region emissions allowance flow, inefficient dynamic linkage and poor price pass-through between the two markets may result in lower volatility spillover effects and dynamic correlations. Highlights: This paper examines the volatility spillover effects between two markets. Energy markets have volatility spillover effects on emission pilots except HBEA. Energy markets demonstrate long-term persistence on Hubei emission pilot. Dynamic correlations for energy and emission price confirm time-varying trend. Dynamic correlations of energy-emission markets exhibit regional differences.